2014
DOI: 10.3390/ani4030409
|View full text |Cite
|
Sign up to set email alerts
|

Large Dog Relinquishment to Two Municipal Facilities in New York City and Washington, D.C.: Identifying Targets for Intervention

Abstract: Simple SummaryWhile the overall trend in euthanasia has been decreasing nationally, large dogs are at a higher risk of euthanasia than other-sized dogs in most animal shelters in the United States. We hypothesized that one way to increase the lives saved with regard to large dogs in shelters is to keep them home in the first place when possible. Our research is the first to collect data in New York City and Washington, D.C., identifying the process leading to the owner relinquishment of large dogs. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 15 publications
(24 reference statements)
1
61
0
Order By: Relevance
“…It is not possible to definitively tell whether the dog acquired the heartworm infection within the zip code of its primary residence, nor is it possible to tell whether the positive heartworm test represents a new or chronic infection due to the long lifespan of the parasite within the host. Despite these limitations, shelter data presents a large, readily available dataset that generally cuts across various human demographics, including income and education levels [45], and is the best data currently available with which to test our predictions. Future studies could partner with local veterinarians to get finer scale host data, as collection of detailed travel history for newly heartwormpositive dogs would allow for more definitive mapping of spatial and temporal host-level incidence trends.…”
Section: Discussionmentioning
confidence: 99%
“…It is not possible to definitively tell whether the dog acquired the heartworm infection within the zip code of its primary residence, nor is it possible to tell whether the positive heartworm test represents a new or chronic infection due to the long lifespan of the parasite within the host. Despite these limitations, shelter data presents a large, readily available dataset that generally cuts across various human demographics, including income and education levels [45], and is the best data currently available with which to test our predictions. Future studies could partner with local veterinarians to get finer scale host data, as collection of detailed travel history for newly heartwormpositive dogs would allow for more definitive mapping of spatial and temporal host-level incidence trends.…”
Section: Discussionmentioning
confidence: 99%
“…People may want to provide a loving home to an animal, but lack knowledge and resources. For example, research has shown people who are in the process of relinquishing their animal to a shelter facility would be open to keeping that animal if help or resources were offered (Weiss et al 2014). 73…”
Section: Policy Recommendationsmentioning
confidence: 99%
“…Of primary importance is access to rental housing. "No-pets" restrictions are a significant obstacle to obtaining affordable housing and a main reason that companion animals are relinquished to shelters (Weiss et al 2014;Shore et al 2003;Patronek et al 1996). One study found:…”
Section: Accessmentioning
confidence: 99%
“…Unrealistic expectations can also lead to relinquishment when people expect the relationship with the pet to stabilize after adoption much quicker than it does [27], to expect the amount of work it takes to care for a pet to be less than it really is [28,29], and to expect the pet to play an unreasonable role in the family-e.g., expecting the pet to keep children busy or to teach them sensitivity and nurturance [23]. Changes of lifestyle during pet ownership can also be a risk factor for relinquishment, be it the addition of new members to the household [26], or moving, housing restrictions, and landlord issues (which are reported as one of the top pet relinquishment reasons [3,[30][31][32][33][34]). The lack of pet care and investment in the relationship is another variable identified as a predictor of pet relinquishment, as it concerns failing to seek veterinary services, behavior classes, or other forms of professional advice [28,29,32].…”
Section: Introductionmentioning
confidence: 99%